Development of Stingless Bee Enterprises in Peatland Ecosystems: A Strategic Approach in Tuwung Village, Pulang Pisau Regency, Central Kalimantan, Indonesia - Pordamantra, Pordamantra; Anggreini, Trisna; Nopembereni, Eti Dewi; Barbara, Betrixia; Sintha, Tri Yuliana Eka (Indonesian Journal of Advanced Research, 2025)
Kelulut bees (Trigona sp.) are a type of honey-producing bee native to Kalimantan, Indonesia, known for their stingless nature. These bees have high economic value, particularly in the peat ecosystem areas. This study aims to analyze the strategy for developing the Kelulut Bee cultivation business in Tuwung Village, Pulang Pisau Regency, Central Kalimantan. Using a quantitative approach and purposive sampling, the study found that one major challenge for breeders is the lack of a definite market and reliance on manual, word-of-mouth marketing. The SWOT analysis revealed that the business is in a weak position (quadrant IV), requiring a survival strategy to avoid failure and improve profitability.